(untitled) (Research, Society and Development, 2022)
The commercialization of ornamental aquatic organisms stands out among the various segments of the Pet market in Brazil. Among the various species used for aquarium hobby, the colored carp, known as Koi or Nishikigoi (Cyprinus Carpio L.), represent the main species commercialized in the country. In this context, the present study carried out a projection of the economic viability of Nishikigoi carp production in a fish farm in the metropolitan region of São Paulo that sells animals to the Brazilian Pet market for ornamental fish. Three hectares of water depth were evaluated during ten production cycles per year. In this period, the total production costs (TC) and effective operating costs (EOC) and total operating costs (TOC) were obtained, plus fixed costs for the operation of this agribusiness. Economic indicators were applied to assess the feasibility of investing in the business through the internal rate of return (IRR), net present value (NPV), payback period (PRC) and cost-benefit ratio of the investment (RCB). The initial investment projection was 2.3 million reais. The most expressive economic viability indicators were obtained by the IRR of 10.41% per year and NPV of approximately 1.6 million reais, considering the net cash flow for the period of ten years. The payback period on invested capital can be reached in 7.15 years with an RCB of 1.68 reais. In this way, the scenario studied demonstrates the feasibility of investing in this agribusiness being a promising venture in the aquaculture sector.